Bibliometric Analysis of Publications on Essential Oil-loaded Nanoparticles as Antibacteria using VOSViewer - Jihan Nurafifah Hernawan; Asep Bayu Dani Nandiyanto (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to analyze the development of the journal Essential Oil-loaded Nanoparticles as Antibacteria with a bibliometric approach using computational mapping analysis using VOSviewer. This study uses data sourced from publications in journals indexed by Google Scholar and collected using the Publish or Perish reference manager application. From the data collection that has been done, it was obtained that 939 journals met the survey criteria. Research developments related to Essential Oil-loaded Nanoparticles as Antibacteria increased slightly in 2013-2015, from 2016 to 2019 it also continued to increase, in 2019 compared to 2020 research publications related to Essential Oil-loaded Nanoparticles as Antibacteria experienced a very large increase significantly, then in 2021 there will be the most publications with a total of 241 articles. Meanwhile, as of September 2022, there were 227 articles related to Essential Oil-loaded Nanoparticles as Antibacteria, although this has decreased from the previous year, this number is still relatively high. Mapping visualizations analyzed in this study consist of Network Visualization, Density Visualization, and Overlay Visualization. The data shows that the popularity of this research tends to be stable, continues to rise and is interesting for further study. This bibliometric analysis can be a new beginning to start research on this topic.